A mini-review on proton conduction of BaZrO3-based perovskite electrolytes. (28th July 2021) - Regalado Vera, Clarita Y; Ding, Hanping; Peterson, David; Gibbons, William T; Zhou, Meng; Ding, Dong
Abstract: Proton conducting ceramics show promise in fuel cells, electrolyzers, permeation membranes, sensor applications, and membrane reactors. Among several types of materials that exhibit proton conduction, perovskite oxides show high proton conductivity at intermediate temperatures, presenting potential benefits for long-term use and lower costs for energy applications. Doped barium zirconate, BaZrO3, is a material that has shown high proton conductivity with encouraging chemical stability. Therefore, it is considered a promising material especially for proton-conducting solid oxide electrochemical cells. Although the proton conduction of doped BaZrO3 has been extensively characterized, the specific phenomena behind its proton conduction are not fully understood. Only recently have specialized techniques and computational tools begun to elucidate the phenomena that determine the conduction properties of the material. In this mini review, an evaluation of the factors affecting the proton conductivity of doped BaZrO3 perovskites and the phenomena governing variations in proton concentration and mobility are presented. Special attention is given to proton interactions with dopants and their resulting effect on hydration and transport properties. Technical strategies are provided to give some guidance on the development of protonic ceramics in energy conversion applications.